2014
DOI: 10.1002/2013ja019457
|View full text |Cite
|
Sign up to set email alerts
|

On the relation of Langmuir turbulence radar signatures to auroral conditions

Abstract: We present a statistical study of anomalous radar echoes observed in the auroral ionosphere thought to be signatures of Langmuir turbulence (LT). Data obtained with the European Incoherent Scatter Svalbard radar during the international polar year (IPY) were searched for these anomalous echoes in the auroral F region. In incoherent scatter radar experiments LT may in certain circumstances be observed as enhanced backscattered radar power at the ion line frequencies, plasma line frequencies, and at zero Doppler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…They found that the anomalous signatures frequently occurred for magnetically disturbed conditions and with a peak occurrence at around 21 MLT. Schlatter et al (2014) found the highest occurrence, as measured over the radar beam width, to be 0.6 % at 21 MLT and for a local K index of 5. Very little data were available for times with a K index above 6, giving insignificant statistics.…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations
“…They found that the anomalous signatures frequently occurred for magnetically disturbed conditions and with a peak occurrence at around 21 MLT. Schlatter et al (2014) found the highest occurrence, as measured over the radar beam width, to be 0.6 % at 21 MLT and for a local K index of 5. Very little data were available for times with a K index above 6, giving insignificant statistics.…”
Section: Introductionmentioning
confidence: 85%
“…The occurrence rates reported by Schlatter et al (2014) suggest that anomalous echoes resembling SLT signatures are frequently observed with the ESR in the disturbed evening sector. Simultaneous magnetometer measurements indicate magnetic disturbances and, thus, possible particle precipitation on a large spatial scale.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…We have not focused here on strongly enhanced plasma lines, related to strong Langmuir turbulence (e.g. Schlatter et al, 2014), which are a topic of separate study.…”
Section: Discussionmentioning
confidence: 99%